Inclusive Education in Lithuania: The Authentic Experience of Youth - Retrospective and Future Perspectives - Targamadzė, Vilija; Kriaučiūnienė, Roma (Journal of Education Culture and Society, 2025)
Aim. The implementation of inclusive education has been explored from various perspectives. Much of the focus has been on the challenges faced by children with special educational needs (SEN) and the potential negative effects on their peers in the classroom. However, there seems to be a gap in research that examines not only the negative aspects but also the positive outcomes of these interactions. Does the presence of children with SEN have a negative impact on their peers, or does their interaction foster positive effects on the classroom environment? The aim of the study is to uncover the authentic experiences of young people in inclusive education when studying with SEN from a retrospective and future perspective, and to highlight their recommendations for those who are currently studying with their classmates with special educational needs. Methods. The study adopts a social constructivist approach, which proposes that individuals build personal understanding based on their experiences, attitudes, and interactions with others and the world. A qualitative research method was applied, structured interviews were conducted, focusing on three key areas: the informant’s positive experiences with a SEN classmate, perceived barriers to communication, and recommendations for current students in classrooms with SEN peers. Results. Analysis of the empirical data revealed that interacting with SEN classmates positively influenced the informants’ personal growth, helping them develop social skills for engaging with SEN individuals. Communication barriers were identified, primarily stemming from a lack of understanding of the nature of SEN disorders and behaviour. However, none of the informants expressed negative attitudes towards their SEN peers; rather, their responses reflected empathy and a genuine willingness to understand and assist them. Conclusions. Empirical research indicates that students studying pedagogy generally view inclusive education positively, though they acknowledge challenges based on their personal experiences of learning alongside peers with special educational needs. Drawing from these experiences, reflections, and acquired knowledge, informants recommend several key practices for students learning with SEN classmates: fostering a positive attitude, understanding their differences and needs, supporting their participation in activities, and assisting with tasks.